2017
DOI: 10.1007/s00246-017-1787-2
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Literature Review on the Incidence and Prevalence of Heart Failure in Children and Adolescents

Abstract: While the epidemiology of adult heart failure has been extensively researched, this systematic review addresses the less well characterized incidence and prevalence of pediatric HF. The search strategy used Cochrane methodology and identified 83 unique studies for inclusion. Studies were categorized according to whether the HF diagnosis was reported as primary (n = 10); associated with other cardiovascular diseases (CVDs) (n = 49); or associated with non-CVDs (n = 24). A narrative synthesis of the evidence is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 79 publications
1
39
0
2
Order By: Relevance
“…Symptomatic atrial septal defects or clinically manifested heart failure has been reported to be present in 11.6-20% of children with atrial septal defect and even more common in children with large atrial septal defects. 33,34 This is in line with our study, as 48 (12%) of the children had symptomatic atrial septal defects. This rules out the risk of selection bias due to overtreatment in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Symptomatic atrial septal defects or clinically manifested heart failure has been reported to be present in 11.6-20% of children with atrial septal defect and even more common in children with large atrial septal defects. 33,34 This is in line with our study, as 48 (12%) of the children had symptomatic atrial septal defects. This rules out the risk of selection bias due to overtreatment in our study.…”
Section: Discussionsupporting
confidence: 90%
“…The other main cause of pediatric HF is cardiomyopathy (predominantly dilated cardiomyopathy), with an estimated annual incidence of 1 per 100,000 children in the US, Australia, United Kingdom (UK), and Ireland [ 11 , 12 , 13 ]. Recently, Shaddy et al have described the incidence of HF ranging from 0.87/100,000 (UK and Ireland), 7.4/100,000 (Taiwan), and 83.3/100,000 (Spain) [ 14 ]. Key findings of their study included a prevalence of HF associated with cardiomyopathies ranging from 36.1% (Japan) to 79% (US); associated with CHD from 8% (Norway) to 82.2% (Nigeria); associated with rheumatic heart diseases from 1.5% (Turkey) to 74% (Zimbabwe); associated with renal disorders from 3.8% (India) to 24.1% (Nigeria); and associated with HIV from 1% (US) to 29.3% (Brazil).…”
Section: Incidence and Prevalencementioning
confidence: 99%
“…Levosimendan povisuje unutarstaničnu koncentraciju kalcija i time ima pozitivno inotropno djelovanje, ali bez aritmogenog učinka. [78][79][80][81][82] Sve se češće indicira njegova primjena u jedinicama intenzivnog liječenja novorođenčadi. U našoj zemlji već se niz godina u nekoliko centara izvodi ehokardiografski probir na prirođene srčane greške.…”
Section: Srčane Greške Ovisne O Arterijskom (Botallovu) Duktusuunclassified